A study of linguistic devices to Attribute source of information in news reports - english vs. Vietnamese (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This thesis investigates linguistic devices to attribute source of information in English and Vietnamese news reports in three aspects: syntax, semantic, and pragmatics. A contrastive analysis was conducted to find out the similarities and differences of reportive markers in English and Vietnamese newspaper language in the three aspects and the frequent level of reportive markers used in English and Vietnamese newspapers. Therefore, descriptive research was the main method for the contrastive analysis. The analysis was carried out with the empirical evidence obtained from English and Vietnamese newspaper corpora of 1000 samples, of which 500 samples in English and 500 ones in Vietnamese were examined. The study was based on Appraisal Theory, the principles of politeness, engagement, epistemic modality and evidentiality. The qualitative and contrastive analysis was done to find out similarities and differences between the two languages in terms of structural and lexical characteristics of attributions, their semantic features such as showing engagement and the scale of reliability as well as their pragmatic features, namely accuracy - orientation, writer/speaker - orientation, and reader/hearer - orientation. The study also provided some implications for teaching and learning as well as suggestions for further research.